Thermal treatment of municipal solid waste incineration fly ash: Impact of gas atmosphere on the volatility of major, minor, and trace elements. (1st August 2020) - Lane, Daniel J.; Jokiniemi, Jorma; Heimonen, Mikko; Peräniemi, Sirpa; Kinnunen, Niko M.; Koponen, Hanna; Lähde, Anna; Karhunen, Tommi; Nivajärvi, Taina; Shurpali, Narasinha; Sippula, Olli
Highlights: Only C and Cu were more volatile in oxidising conditions. Sn and Sb only volatilised in reducing conditions. Bi, Cd, Pb, S, and Zn became volatile at lower temperatures in reducing conditions. Rates of release of Cl, K, and Na were greater in reducing conditions. Equilibrium calculations poorly predict the behaviour of S and most trace elements. Abstract: Development of thermal processes for selective recovery of Zn and other valuable elements from municipal solid waste incineration (MSWI) fly ash requires comprehensive knowledge of the impact of gas atmosphere on the volatile behaviour of the element constituents of the ash at different reaction temperatures. This study assesses the partitioning of 18 elements (Al, As, Bi, C, Ca, Cd, Cl, Cu, K, Mg, Na, P, Pb, S, Sb, Sn, Ti, and Zn) between condensed and gaseous phases during thermal treatment of MSWI fly ash in both oxidising gas and reducing gas atmospheres, at different temperatures spanning the range 200–1050 °C. The operating atmosphere had major impacts on the partitioning of the following elements: As, Bi, C, Cd, Cu, Na, Pb, S, Sb, Sn, and Zn. The partitioning of these elements cannot be accurately predicted over the full range of investigated operating conditions with global thermodynamic equilibrium calculations alone, i.e. without also considering chemical kinetics and mass transfer. In oxidising conditions, the following elements were predominately retained in condensed phases, even at high temperatures: As, Bi, Sb, Sn, and Zn. All these elements, except As, were largely released to the gas phase (>70%) at high temperatures in reducing conditions. The impact of gas atmosphere on the volatility of Cd and Pb was greatest at low reaction temperatures (below ~750 °C). Results for volatile matrix elements, specifically C, Cl, K, Na, and S, are interpreted in terms of the mechanisms governing the release of these elements to the gas phase.